FAKTOR-FAKTOR YANG DAPAT MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN CONSUMER NON-CYCLICALS - Mario Devan; Agustin Ekadjaja (Jurnal Paradigma Akuntansi, 2026)
This investigation was done with the aim of gathering empiricall evidence on the effect of Profitability, Leverage, Firm Size, and Growth Opportunities on Cash Holding. Consumer non cyclicals companies that listed on the Indonesia Stock Exchange (IDX) for the period 2019-2021 are the subjects that will be used in this investigation. The experiment was performed out on 90 data from 30 samples of consumer non cylicals companies that were processed using the purposive sampling technique. EViews ver 12.0 programs will be used for processing the data. The investigation conducted shows that profitabillity and Firm Size do not have a significant positive effect on Cash Holding, Leverage has a significant positive effect on Cash Holding, and growth opportunity do not have a significant negative effect on cash holding.